2021
DOI: 10.46300/91011.2021.15.16
|View full text |Cite
|
Sign up to set email alerts
|

Composition And Diversity Of Plant Species In The Two Types Of Land Cover Of Natural Laboratory Of Hampangen Educational Forest

Abstract: Forests are natural resources that contribute to sustaining life support systems. The purpose of this study was to determine the composition and diversity of plant species in the Hampangen Educational Forest Nature Laboratory with the object of research on plant species diversity at growth rates of seedlings, poles, saplings, and trees in the observation plots of secondary swamp forest and swamp scrub. The research was conducted using a combination technique of paths and checkered lines in each of the 30 measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…The plant species that have the highest IVI are due to their higher density, frequency, and dominance than other types. The higher the IVI of a species, the higher the level of control in the community of that species grows, Similar result was conducted by another Author Sosilawatyet al [12] on the other study [13] revealed that the IVI values show variation in ecologically dominant from site to site. Hence, the IVI has helped in understanding the ecological significance of the species in the tropical dry deciduous forest[14].…”
Section: Resultssupporting
confidence: 82%
“…The plant species that have the highest IVI are due to their higher density, frequency, and dominance than other types. The higher the IVI of a species, the higher the level of control in the community of that species grows, Similar result was conducted by another Author Sosilawatyet al [12] on the other study [13] revealed that the IVI values show variation in ecologically dominant from site to site. Hence, the IVI has helped in understanding the ecological significance of the species in the tropical dry deciduous forest[14].…”
Section: Resultssupporting
confidence: 82%